The Development of Family Law Materials in Bahtsul Masail Nadhlatul Ulama - Agus Setiawan; Ibnu Akbar Maliki (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2020)
Family law has a very important position in Islam. Its position as the core of sharia is related to the assumption that family law is a gateway to understanding more about Islam. The reform of Islamic family law in Indonesia has gone through a long and long process. In the process of its formation, the material for family law in Indonesia was taken from various sources, such as fiqh books, fatwas, and other sources of Islamic law. Nahdatul Ulama (NU) is one of the Islamic organizations in Indonesia that has contributed to the development of Islamic family law material. One of NU's real contributions in enriching material on Islamic family law in Indonesia is through the Lajnah Bahtsul Masail (LBM) forum. This paper will discuss the development of family law materials through the Lajnah Bahtsul Masail forum. This paper is the result of qualitative research. Sources of data in this study consisted of primary and secondary data. Analysis of the data in this study using content analysis method. Bahtsul masail as the collective ijtihad of NU members has made a real contribution to the development of Islamic family law material in Indonesia. Various new phenomena that arise both due to technology and cultural differences have received fiqh answers through bahtsul masail. This is indicated at least by the similarities between several legal decisions and the marriage law in Indonesia.